IMPROVING SPEAKING SKILL BY USING UPIN AND IPIN ENGLISH VERSION - Muzdalifah, Indah; Asril, Elvira (TELL - US JOURNAL, 2020)
Technology has been part of human life. It can connect to English Language Learning. One of them is video animation, such as serial cartoon Upin Ipin English version. However, it only can be found in YouTube This research aims to find out whether Upin Ipin serial cartoon movie can improve students’ ability in speaking English. The method of this research was using descriptive qualitative research by collecting the data through pretest and posttest and described them into detail explanation. Then they were compared between pretest and post-test. The result is the 48,8 in pretest and 57,77 for the post-test. It means there is an improvement.